P3.18 COMPARISON OF STRUCTURAL AND FUNCTIONAL CAROTID AND AORTIC CHANGES IN DIABETES MELLITUS AND HYPERTENSION - Zbigniew Bociąga*; Joanna Jaroch; Ewa Kruszyńska; Maria Łoboz-Rudnicka; Barbara Rzyczkowska; Krystyna Łoboz-Grudzień (Artery Research, 2015)
Background: It is known that age, blood pressure and diabetes mellitus are determinants of arterial stiffness. There are no studies comparing impact of hypertension and diabetes on structural and functional carotid and aortic changes. Aim: The aim of the study was to evaluate structural and functional carotid and aortic changes in patients with diabetes without hypertension and patients with hypertension without diabetes. Materials and methods: The study group consisted of 64 subjects without manifest cardiovascular disease (43 M and 21 F), mean age 54± 10,4 years. Control group consisted of 40 healthy subjects. Patients were divided into two groups: group A with diabetes without hypertension (n=32), group B with hypertension without diabetes (n=32). From carotid arteries ultrasound – IMT and from carotid arteries – high-resolution echo-tracking (eT) local arterial stiffness parameters were evaluated: β-beta, Ep – epsilon, AI- augmentation index, PWV β-one-point pulse wave velocity; also aortic stiffness parameters: aortic distensibilty, beta – aortic stiffness and aortic pressure strain elastic modulus Ep were calulated. Results: In group A and group B mean values of IMT, eT and aortic stiffness indices were statistically significantly higher than in control group. There was no significant differences in mean values of IMT, eT and aortic stiffness indices between two groups. Conclusions: Impact of diabetes and hypertension on structural and functional carotid and aortic changes is equal.